2022
DOI: 10.1109/access.2022.3194145
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Literature on Automated Sleep Scoring

Abstract: Sleep is a period of rest that is essential for functional learning ability, mental health, and even the performance of normal activities. Insomnia, sleep apnea, and restless legs are all examples of sleep-related issues that are growing more widespread. When appropriately analyzed, the recording of bio-electric signals, such as the Electroencephalogram, can tell how well we sleep. Improved analyses are possible due to recent improvements in machine learning and feature extraction, and they are commonly referr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 146 publications
0
5
0
Order By: Relevance
“…Automated EEG decision-support tools are also becoming available (e.g. seizure surveillance) [10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Automated EEG decision-support tools are also becoming available (e.g. seizure surveillance) [10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…However, studies in recent years have focused on specific aspects of the problem. For example, in [ 17 ], only the algorithms that work with the EEG signal were selected. In [ 18 ], consumer sleep technologies (CSTs) were investigated to analyse sleep in combination with artificial intelligence.…”
Section: Introductionmentioning
confidence: 99%
“…Spectral linear features and an RF classifier led to the best classification performance, while ensuring real-time online processing. An extensive review of the current literature on automated sleep scoring can be found in [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%